Phenotypic variability and genetic diversity analysis of cultivated potatoes in China - Hu, Jun; Mei, Meng; Jin, Fang; Xu, Jianfei; Duan, Shaoguang; Bian, Chunsong; Li, Guangcun; Wang, Xiyao; Jin, Liping (Frontiers in Plant Science, 2022)
Phenotypic evaluation and molecular biotechnology are both important in the identification and utilization of crop germplasm resources. In this study, the phenotypic variation and genetic diversity of 149 main potato cultivars in China were investigated with 12 phenotypic traits and 24 SSR markers. The coefficient of variation of 12 phenotypic traits ranged from 12.11% to 156.93%. The results of SSR markers exhibited a relatively high level of genetic variation (Na =5.458±1.499, Ne =3.300±1.087, I =1.397±0.298, Ho =0.797±0.178, He = 0.660±0.117, and PIC=0.702±0.087). Population structure and phylogenetic tree analysis divided the varieties into three subgroups. The results indicated that ninety percent of the molecular variance was attributed to within-group differences, and the remaining 10% was attributed to variation among groups. Consistent with previous report, alleles of the STI032 marker were significantly associated with tuber starch content and growth period traits in the population. The results of this study could facilitate the utilization of potato germplasm resources, molecular genet ic breeding and improvement.